Education without a republic. Milestones of Peruvian education in the last century - Tovar Samanez, Teresa (2020)
Retrospective of Peruvian education in the last century, which distinguishes four demarcating milestones: 1. Education as a privilege in oligarchic society; 2. The crisis of the oligarchic state and a new order in education; 3. The counter-reform and the commodification of education and social rights; and 4. The civilizational crisis and the questioning of the neoliberal educational model. The article makes a reading of the relationship of education with power, with society and with the process of transformation of the country. Starting from a combined analysis of five components, a general and articulating interpretation of what happened in Peruvian education in the last century is attempted. These components are: political time, the role of the State, the right to education and the priority of education on the agenda. It is possible to visualize the advances and setbacks of a process that does not follow a constant progressive path and that lacks an institutional and democratic base.